#TITLE_ALTERNATIVE# - DEVI DIANANTARI (NIM 13204138), PARAMITA
This Final Project used LS and LMS algorithm for the channel estimation and equalization technique in mobile WiMAX system. LS algorithm is the simplest but least accurate for time varying channel. LMS algorithm is an improvement of LS algorithm which adaptive with time varying channel. Evaluation is by learning the BER vs. SNR graph in each algorithm to acknowledge the influence of user velocity and appropriate pilot length interval for this system. From this evaluation derived that the system which use channel estimation and equalization technique with LMS algorithm gives better performance than LS algorithm. High user velocity shows performance system degradation. For system with channel bandwidth 5 MHz and 512 point FFT which use channel estimation and equalization technique with LMS algorithm, the appropriate pilot length interval with comb type inserting technique is 8.